2016
DOI: 10.1016/j.apjtm.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect and molecular mechanism of mir-146a on proliferation of lung cancer cells by targeting and regulating MIF gene

Abstract: miR-146a has low expression in NSCLC tissues and cell lines, while MIF has the over expression in NSCLC tissues. The increased expression of miR-146a can inhibit the expression of MIF via the gene targeting and thus inhibit the proliferation of A549 cells and induce the apoptosis of cancer cells, which may be realized through NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This might arise from the inhibition of cell proliferation, differentiation, and migration by miR-146a through regulating several pathways. [ 20 , 23 ] In addition, we also found that high expressions of tissue miR-146a and plasma miR-146a were associated with better OS, whereas only tissue miR-146a high expression was an independent factor for prolonged OS of ICC patients. There are 2 possible reasons.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This might arise from the inhibition of cell proliferation, differentiation, and migration by miR-146a through regulating several pathways. [ 20 , 23 ] In addition, we also found that high expressions of tissue miR-146a and plasma miR-146a were associated with better OS, whereas only tissue miR-146a high expression was an independent factor for prolonged OS of ICC patients. There are 2 possible reasons.…”
Section: Discussionmentioning
confidence: 59%
“…Upregulation of miR-146a inhibits lung cancer cell proliferation and differentiation via mediating the macrophage migration inhibitory factor (MIF) gene and NF-κB signaling pathway. [ 20 ] Also, its overexpression represses gastric cancer cell migration by reducing the UHRF1 level via targeting its 3′-UTR, resulting in the inhibition of tumor invasion and metastasis subsequently. [ 21 ] Additionally, miR-146a expression has been observed to be positively associated with antitumor immune systems by targeting signal transducer and activator of transcription 3 (STAT3) in human hepatocellular carcinoma (HCC) cells.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in the regulation of diverse biological processes, including invasion, migration, proliferation and cell apoptosis ( 14 16 ). Abnormal expression of miRNAs, including the upregulation of miR-429 ( 17 ), miR-19a ( 18 ) and miR-146a ( 19 ), and downregulation of miR-143 ( 20 ), miR-3666 ( 21 ) and miR-29b ( 22 ) have been detected in lung cancer. Thus, miRNAs have potential as biomarker for diagnosis, targeted therapy and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2013, Chen et al (37) reported that the expression of miR-146a was reduced in NSCLC, which suggested that miR-146a may have a role as a tumor suppressor gene. Wang et al (38) showed similar results. These data indicated that, in lung cancer, the role of miR-146a and whether it acts as an oncogene or a tumor suppressor gene remains debatable.…”
Section: Discussionmentioning
confidence: 62%